Use of oat beta-glucan and yerba mate in capsules reduces anthropometric measurements in patients with metabolic syndrome - Nunes, Paula Lorenzoni (2025)
Introduction: Metabolic Syndrome is composed of a set of metabolic alterations, and alternatives have been sought in phytotherapy, with emphasis on white oats and yerba mate. Objective: To analyze the impact of supplementation with beta-glucan capsules, extracted from oats, and standardized dry extract of yerba mate on anthropometric variables in patients with metabolic syndrome. Methodology: Randomized, double-blind clinical trial, with a quantitative and analytical approach, with 26 patients, divided into group beta-glucan 1g/day (n=9), group I. paraguariensis 2.25g/day (n=5), beta-glucan group + I. paraguariensis 1g/day + 2.25g/day (n=6) and placebo group 250mg/day of starch (n=6), followed for 90 days. Weight, body composition, height and anthropometric measurements were evaluated. Results: There was a significant reduction in weight and BMI in patients using beta-glucan, but a significant increase in abdominal circumference. In addition, the group that used the combination of beta compounds and herb showed a significant increase in waist and hip circumference, in addition to an increase in visceral fat. Conclusion: Only the use of herbal medicines is not enough to reduce anthropometric measurements, requiring studies of their association with changes in life habits and physical exercises, in order to reduce the factors that make up the metabolic syndrome, as well as to improve the quality of life. life by preventing the development of cardiovascular diseases.